International trade and technological competition in markets with dynamic increasing returns - Luca Fontanelli; Mattia Guerini; Mauro Napoletano (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
We build a simple dynamic model to study the effects of technological learning, market selection and international competition in the determination of export flows and market shares. The model features two countries populated by firms with heterogeneous productivity levels and sales. Market selection in each country is driven by a finite pairwise Pólya urn process. We show that market selection leads either to a national or to an international monopoly in presence of a static distribution of firm productivity levels. We then incorporate firm learning and entry-exit in the model and we show that the market structure does not converge to a monopoly. In addition, we show that the extended model is able to jointly reproduce a wide ensemble of stylized facts concerning intra-industry trade, industry and firm dynamics.
Keywords: C15; F1; L1; 330; International trade; industrial dynamics; firm dynamics; market selection; Pólya urn